2016
DOI: 10.1074/jbc.m116.753384
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Allosteric HIV-1 Integrase Inhibitors Identified by Crystallographic Fragment Screening of the Catalytic Core Domain

Abstract: Edited by Norma Allewell HIV-1 integrase (IN) is essential for virus replication andCollectively, our findings provide a plausible path for structurebased development of second-generation ALLINIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Clinical mutations were found not only at the direct drug-binding sites but also non-functional regions [79], the latter of which can have indirect effects on drug resistance such as allosteric communication to the catalytic sites. The inhibition of such communication can be explored for novel classes of drugs, such as in the case of reverse transcriptase inhibitors (RTIs) [80], integrase inhibitors [81], and protease inhibitors (PIs) [82]. The non-nucleoside RTIs bind non-competitively to an allosteric site on p66 subunit to cause structural changes in the RT polymerase active site, hindering DNA polymerization.…”
Section: Analysis Of Allosteric Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical mutations were found not only at the direct drug-binding sites but also non-functional regions [79], the latter of which can have indirect effects on drug resistance such as allosteric communication to the catalytic sites. The inhibition of such communication can be explored for novel classes of drugs, such as in the case of reverse transcriptase inhibitors (RTIs) [80], integrase inhibitors [81], and protease inhibitors (PIs) [82]. The non-nucleoside RTIs bind non-competitively to an allosteric site on p66 subunit to cause structural changes in the RT polymerase active site, hindering DNA polymerization.…”
Section: Analysis Of Allosteric Communicationmentioning
confidence: 99%
“…Our ongoing study has found further potential interferences targeting the p51 to affect overall RT activity [83]. On integrase, allosteric inhibitors impair the binding of integrase and the cellular cofactor LEDGF/p75 during HIV-1 replication to induce aberrant integrase multimerization [81]. Similarly, a potential allosteric protease inhibitor was found to bind to a site at the protease flap to equipotently inhibit both wild-type and certain drug-resistant variants [82].…”
Section: Analysis Of Allosteric Communicationmentioning
confidence: 99%
“…Allosteric effects can underlie both drug resistance and inhibition mechanisms that can be explored for novel classes of drugs to develop novel classes of reverse transcriptase inhibitors (RTIs) [81], integrase inhibitors [82], and protease inhibitors (PIs) [83]. For example, non-nucleoside RTIs are known to bind non-competitively to an allosteric site on p66 subunit to cause structural changes to the RT polymerase active site, hindering DNA polymerization.…”
Section: Emerging Drug Resistance Mutations Considered As Allosteric mentioning
confidence: 99%
“…Studies suggested the RT p51 subunit, in addition to p66, to be also involved in allosteric couplings upon inhibitor binding [81,84]. Allosteric integrase inhibitors can impair the binding of integrase and the cellular cofactor LEDGF/p75 during HIV-1 replication and induce aberrant integrase multimerization [82]. Similarly, a potential allosteric modulator of HIV-1 protease was found to bind to an allosteric site at the protease flaps and equipotently inhibit both wild-type and certain drug resistant variants [83].…”
Section: Emerging Drug Resistance Mutations Considered As Allosteric mentioning
confidence: 99%
“…IN strand transfer inhibitors (INSTIs) 3 – 6 , together with allosteric inhibitors of IN 7 13 , efficiently inhibit viral replication. Allosteric inhibitors correspond to noncatalytic site inhibitors of IN and may interfere with distinct steps than integration, whereas INSTIs target the active site of IN and consistently inhibit the overall integration process by specifically blocking the ST reaction.…”
Section: Introductionmentioning
confidence: 99%